Pulsed Field Ablation for the Treatment of Atrial Fibrillation: PULSED AF Pivotal Trial - Verma, Atul; Haines, David E.; Boersma, Lucas V.; Sood, Nitesh; Natale, Andrea; Marchlinski, Francis E.; Calkins, Hugh; Sanders, Prashanthan; Packer, Douglas L.; Kuck, Karl-Heinz; Hindricks, Gerhard; Onal, Birce; et al. (Circulation (New York, N.Y.), 2023)
Pulsed field ablation uses electrical pulses to cause nonthermal irreversible electroporation and induce cardiac cell death. Pulsed field ablation may have effectiveness comparable to traditional catheter ablation while preventing thermally mediated complications. The PULSED AF pivotal study (Pulsed Field Ablation to Irreversibly Electroporate Tissue and Treat AF) was a prospective, global, multicenter, nonrandomized, paired single-arm study in which patients with paroxysmal (n=150) or persistent (n=150) symptomatic atrial fibrillation (AF) refractory to class I or III antiarrhythmic drugs were treated with pulsed field ablation. All patients were monitored for 1 year using weekly and symptomatic transtelephonic monitoring; 3-, 6-, and 12-month ECGs; and 6- and 12-month 24-hour Holter monitoring. The primary effectiveness end point was freedom from a composite of acute procedural failure, arrhythmia recurrence, or antiarrhythmic escalation through 12 months, excluding a 3-month blanking period to allow recovery from the procedure. The primary safety end point was freedom from a composite of serious procedure- and device-related adverse events. Kaplan-Meier methods were used to evaluate the primary end points. Pulsed field ablation was shown to be effective at 1 year in 66.2% (95% CI, 57.9 to 73.2) of patients with paroxysmal AF and 55.1% (95% CI, 46.7 to 62.7) of patients with persistent AF. The primary safety end point occurred in 1 patient (0.7%; 95% CI, 0.1 to 4.6) in both the paroxysmal and persistent AF cohorts. PULSED AF demonstrated a low rate of primary safety adverse events (0.7%) and provided effectiveness consistent with established ablation technologies using a novel irreversible electroporation energy to treat patients with AF. URL: https://www. gov; Unique identifier: NCT04198701.